2010
DOI: 10.1007/s11051-010-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nano-TiO2 on seed germination, development and mitosis of root tip cells of Vicia narbonensis L. and Zea mays L

Abstract: This study aimed to provide new information about phyto-toxicology of nano-TiO2 on plant systems. To contribute to the evaluation of the potential harmful effects of the nanoparticles on monocots and dicots we considered their effects on seed germination and root elongation applying a concentration range from 0.2 to 4.0% in the plants Zea mays L. and Vicia narbonensis L. Moreover, we achieved a genotoxicity study at cytological level in root meristems by means of traditional cytogenetic approach, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
116
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(130 citation statements)
references
References 22 publications
13
116
0
1
Order By: Relevance
“…There is a controversy for health risk and benefits of nanoparticles on both flora and fauna (USEPA 2007). Nanotechnology is absolutely a new emerging field, and basically there are evidences of several negative effects on growth and development of plantlets (Castiglione et al 2011). Previous research highlighted on the phytotoxicity of nanoparticles in different medium such as agar medium, filter paper on petri dish and soil for seed germination and root elongation (Zheng et al 2005;Khodakovskaya et al 2009;Doshi et al 2008;Song et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is a controversy for health risk and benefits of nanoparticles on both flora and fauna (USEPA 2007). Nanotechnology is absolutely a new emerging field, and basically there are evidences of several negative effects on growth and development of plantlets (Castiglione et al 2011). Previous research highlighted on the phytotoxicity of nanoparticles in different medium such as agar medium, filter paper on petri dish and soil for seed germination and root elongation (Zheng et al 2005;Khodakovskaya et al 2009;Doshi et al 2008;Song et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Hatami et al (2014) reported that the use of appropriate concentration of nano-TiO 2 increased seed germination characteristics and early growth of medicinal and aromatic plants compared to control and baulk treatments. However, some studies have reported negative effects of TiO 2 -nano-particles on higher plants that varied between plant tissues, growth stages, plant species, applied concentrations, and specific properties of nano-particles (Castiglione et al 2011). Thus, the exploration of their extensive application in agriculture and plant science is still in debate (Kurepa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the field of medicinal and aromatic plants, the use of nanomaterials is relatively new and needs more researches. However, some studies have reported negative effects of TiO 2 nanoparticles (NT) on higher plants that varied between plant tissues, growth stages, plant species, applied concentrations, and specific properties of nanoparticles (Castiglione et al, 2011). Thus, the exploration of their extensive application in agriculture and plant science is still in debate (Kurepa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%